Can China's national comprehensive medical reform increase medical resources and reduce healthcare burden: evidence from Chinese provinces - Xiangyu Fu; Xiangyu Fu; Xiang Ren; Xiang Ren; Qirui Chen (Frontiers Media S.A., 2024)
ObjectivesChina's national comprehensive medical reform (NCMR) is an important attempt in the reform of healthcare system, and quantitative evaluation of its effect is of great significance for continuously deepening medical reform, grasping the reform direction, and building a healthy China. Therefore, focusing on medical resources and medical burden, this study aims to systematically explore the policy effectiveness and the provincial heterogeneity of NCMR, as well as the potential influencing factors.MethodsUtilizing the collected multi-period panel data of 31 provinces in mainland China in 2006-2021, we regarded the release of the two batches of pilot provinces in NCMR as a quasi-natural experiment and comprehensively adopted a Staggered difference-in-differences (DID) model and Synthetic Control Method (SCM), combined with word frequency statistics and grouping regression analysis.ResultsNCMR can effectively increase the number of licensed physicians by 12.6% and reduce the per capita medical expense for in-patients by 7.2% in the pilot provinces. Furthermore, the NCMR policy effect in different pilot provinces shows various characteristics, and only Jiangsu, Zhejiang, and Chongqing achieve both the growth of medical resources and the reduction of medical expenditure. Meanwhile, word frequency statistics are conducted based on related policy descriptions and news reports on the official websites, so as to summarize the specific policy means in the three provinces, and provide a reference for other provinces to practice the healthcare reforms. Besides, extensibility analysis shows that the effect of NCMR is affected by the population aging and health status. Groups with low degree of population aging (low-AG)/high population health status (high-HE) performed a more obvious reform effect.ConclusionThis study provides beneficial policy implications for increasing medical resources, reducing medical burden, and promoting medical reform process.